MENINGKATKAN KETERAMPILAN PASSING BAWAH MENGGUNAKAN LATIHAN BERVARIASI PADA SISWA PESERTA EKSTRAKURIKULER BOLAVOLI SMK NEGERI 2 SINGOSARI KABPATEN MALANG - Asri Widiyaraya Anggraini; Agus Tomi; Sulistyorini Sulistyorini (Fakultas Ilmu Keolahragaan UM)
Abstract: This study aims to improve the quality of passing down, so that the athletes have the confidence to play and can cope with the attack of an opponent by using a variety of exercises. The study, using action research these sports have in common with action research. The procedure used in this study have similarities with the phases of action research including planning, implementation, observation, reflection. Results of this study was obtained from the 30 athletes, with details of the first 3 weeks for 3 cycles 1 and the second week to cycle 2. The results obtained in the last week, the position of the foot of 93.4%, 93.4% hand position, body position 93.4% , 93.4% impact ball, the ball is 93.4%. With these results under the passing skills can be expressed very well and reached a maximum thoroughness.Keywords: Volleyball game, low passing, training variation